A hierarchical nickel-iron hydroxide nanosheet from the high voltage cathodic polarization for alkaline water splitting. (22nd September 2022) - Lai, Changgan; Zhou, Huan; Ji, Shuai; Guo, Zhiliang; Sun, Jian; Wang, Helin; Nie, Liu; Zhang, Donghuai; Li, Fajun; Lei, Lixu
Abstract: Developing efficient and stable oxygen evolution reaction (OER) electrocatalysts is a promising method to relieve the pressure of noble metals for catalyzing water splitting. Among the prominent candidates, nickel-iron layered double hydroxides (NiFe-LDH) have been found excellent catalytic activity, but their poor conductivity and stability seriously impede their performance. Herein, we report hierarchical NiFe-LDH nanosheets prepared from NiFe-Alloy on nickel mesh (NM) by high voltage cathodic polarization. The resultant NiFe-LDH/NM exhibits a remarkable OER activity and stability, which has a low overpotential of 340 mV at a current density of 10 mA cm −2, and maintains a current density of 15 mA cm −2  at a constant voltage of 1.56 V for 50 h if the NiFe-Alloy/NM is used as the cathode. The successful conversion of NiFe-LDH nanosheets originating from NiFe-Alloy nanoparticles would open a new avenue for synthesizing transition metal-based LDH compounds. Highlights: A novel strategy was reported to gain NiFe-LDH nanosheets by high voltage cathodic polarization. The unique hierarchical nanosheet structure increases the number of accessible active sites. The NiFe-LDH/NM exhibits excellent OER activity and stability in alkaline water splitting. The assembled water splitting electrolyzer shows satisfactory electrochemical properties.